Quality of life and retention in care among people living with HIV initiated on ART in the era of “Universal Test and Treat” policy at a large HIV Clinic in South Western Uganda - Faith Tumuhairwe; Jonathan Izudi; Abel Munina; Anthanasio Bashaija; Francis Bajunirwe (PLoS ONE, 2025)
Background Anti-retroviral therapy (ART) improves the quality of life (QoL) among people living with human immunodeficiency virus (PLWH). Most studies documenting the gains in QoL have been conducted among persons starting treatment at advanced HIV disease. In the era of Universal Test and Treat (UTT) policy, most PLWH start ART early with high CD4 counts. Therefore, we investigated the association between baseline CD4 count with QoL and retention among PLWH during UTT in southwestern Uganda. Methods Between June 11, 2019, and June 10, 2020, we reviewed medical records for PLWH initiated on ART between April 2017 and September 2018 and interviewed them to collect QoL data. The primary exposure was CD4 count at ART initiation categorized as <500 cells/µl (low) versus ≥500 cells/µl (high). Physical and mental health-related QoL were the primary outcomes. Retention was the secondary outcome. Binary logistic regression was used to assess the association between the exposure and the primary outcome, while the Cox Proportional Hazard regression model was used for the secondary outcome. Results Of 300 participants, 59.7% initiated ART at a low baseline CD4 count. ART initiation at a higher baseline CD4 count, compared to a lower baseline CD4 count, was associated with a lower mental health-related QoL (adjusted odds ratio [aOR] 0.56, 95% confidence interval [CI] 0.32–0.97) but similar physical health-related QoL (aOR 0.54, 95% CI 0.10–2.78) and retention (adjusted hazard ratio [aHR] 0.30, 95% CI 0.08–1.14). Conclusion In this cohort of PLWH on ART, those who initiated the treatment at a higher baseline CD4 were less likely to have good mental health-related QoL functioning compared to those initiating at lower CD4 counts. However, the two groups were comparable in physical health-related QoL and retention in care. PLWH initiating ART at a higher baseline CD4 may require mental health-related support as part of treatment.